Mimicry, Ambivalence, and Hybridity of Lazlo Strange Character in Laini Taylor’s Strange the Dreamer - Pramudya Lazuardi; Arido Laksono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
The study aims to describe which aspects represent mimicry, ambivalence, and hybridity using Homi K. Bhabha’s postcolonial studies. This research applies a qualitative analysis method. The primary source of the research data is the novel entitled Strange the Dreamer by Laini Taylor as the object of the study. In contrast, the secondary sources are books and journals related to the study that serves as the primary reference regarding the theory of Bernstein’s heroism and Bhabha’s postcolonialism. To collect the data, the writer uses the close-reading method. This study indicates that the journey of the main character of Strange the Dreamer, Lazlo Strange, is intertwined with postcolonialism issues that develop his act of mimicry, ambivalence, and hybridity.Keywords: postcolonialism; mimicry; ambivalence; hybridity; Lazlo Strange